PEMIDANAAN TERHADAP GELANDANGAN (ANALISIS PASAL 505 KUHP DAN MAQASYID SYARIAH) - Adi Syahputra Sirait (Institut Agama Islam Negeri Padangsidimpuan, 2018)
The homelessness phenomenon becomes homework that requires the central and regional governments to as known that provide solutions, immedietly. It is caused of their existence continues to grow along with the high level of poverty, as known that poverty is the main reason of urbanites from rural areas to the city in hopes of getting jobs and can change their lives. Unfortunity most of them come without education and expertise, thus requiring them to take odd jobs in order to full their needs. Their presence is not expected by all parties. Islam strongly forbids them become beggars, even inside Undang – Undang Dasar 1945, it is clearly stated that their existence is the responsibility of the government. Than, in positive law in Indonesia also expressly provides criminal sanctions for those who carry out tramps with imprisonment sanctions of 3 to 6 months in accordance with article 505 of the KUH Code. The problem of homelessness is also regulated in Islam. Yusuf Qardhawi said that the government may give criminal ta'zir for homeless, because their deeds are not honorable. The honor is very protected in Islam, namely the hift al-ird (guarding honor) which is one of the dhururiah's needs.